The training experiences of black counsellors - Watson, Valerie V. (2004)
There has been a significant expansion of counselling and psychotherapy training programmes within higher education and the independent training sector. The curriculum content for counselling and psychotherapy training is largely unregulated at a national level, and yet qualified counsellors are expected to cater for 'clients' with wide ranging needs and from a diversity of cultural backgrounds.